2018
DOI: 10.1002/cjoc.201800330
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Benzofuran‐fused 1,4‐Dihydropyridines via Bifunctional Squaramide‐catalyzed Formal [4+2] Cycloaddition of Azadienes with Malononitrile

Abstract: An efficient bifunctional squaramide‐catalyzed Michael addition/cyclization of azadienes with malononitrile has been successfully developed, providing a facile access to chiral benzofuran‐fused 1,4‐dihydropyridines with excellent yields, wide substrate scope and up to 99% ee. Additionally, this formal [4+2] cycloaddition can be performed in gram scale without noticeable loss of yield and enantioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 101 publications
0
13
0
Order By: Relevance
“…Since the seminal work by Zhao, 2‐arylidene‐ N ‐tosylbenzofuran‐3(2 H )‐imines have been successfully employed in the organocatalytic asymmetric reactions of allene ketones, phosphites, tritylthiol, malononitrile, isatin‐derived enals, and 3‐chlorooxindoles, respectively. Recently, we have achieved the organocatalytic enantioselective Michael additions of these 1‐azadienes with rhodanines and γ‐substituted deconjugate butenolides .…”
Section: Methodsmentioning
confidence: 99%
“…Since the seminal work by Zhao, 2‐arylidene‐ N ‐tosylbenzofuran‐3(2 H )‐imines have been successfully employed in the organocatalytic asymmetric reactions of allene ketones, phosphites, tritylthiol, malononitrile, isatin‐derived enals, and 3‐chlorooxindoles, respectively. Recently, we have achieved the organocatalytic enantioselective Michael additions of these 1‐azadienes with rhodanines and γ‐substituted deconjugate butenolides .…”
Section: Methodsmentioning
confidence: 99%
“…[59] In 2018, Zhou's group reported that the combination of malononitrile 59 and azadienes 41 could synthesize chiral benzofuran-fused 1,4dihydropyridine 82 from the asymmetric formal cycloaddition, with catalysis by the bifunctional squaramide Cat-19 (Scheme 14a). [60] This reaction has excellent enantioselectivities and a broad substrate scope. Donor-acceptor cyclopropanes (DACs) have become a powerful tool for the construction of cyclic compounds, which often undergo [3 + n] cycloaddition reactions.…”
Section: α β-Unsaturated Iminesmentioning
confidence: 99%
“…Aurone-derived azadienes have been regarded as a pivotal class of highly reactive intermediates in organic synthesis due to the driving force of aromatization [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. In the past few years, only a few catalytic asymmetric processes of azadienes have been successfully developed on the basis of transition-metal catalysis and organo-catalysis [10][11][12][13][14][15][16][17][18][19][20]. Zhao and co-workers [10][11][12] disclosed palladium-catalyzed asymmetric formal cycloaddition of azadienes to prepare medium-sized compounds including benzofuran-fused nine-membered and ten-membered heterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, chiral Brønsted bases have been used as highly enantioselective bifunctional catalysts for the asymmetric nucleophilic addition of phosphites, thiols and rhodanines to azadienes [17][18][19]. Additionally, the formal [4+2] cycloaddition of azadienes with malononitrile using bifunctional squaramide as catalyst has been realized by our group [20] (Scheme 1a). Although considerable progress has been achieved in asymmetric reactions of azadienes, the organocatalytic systems are still limited.…”
Section: Introductionmentioning
confidence: 99%